Planning Analysis Of Post-Limestone Mining Area Conservation Program In Bedoyo Sub-District - Febriana Muryanto; Monesta Cici Ijan; Suryandari, Suryandari; Munawara Salfitri; Ari Dyah Sinta Tri Astuti (Cita konsultindo, 2024)
This research analyzes the planning of a post-limestone mining area conservation program in Bedoyo Kalurahan. The main objective of this research is to identify an appropriate conservation program for the post-limestone mining area in Bedoyo Kalurahan and implement it Bedoyo Kalurahan and implement the program. This research usesdescriptive qualitative research methods, while the data generated is descriptive data in the form of interviews, observations and documentation from the object under study. The results showed that there is a conservation program that is suitable to be carried out on post-mining land in Bedoyo Village is post-mining land rehabilitation with reforestation.